WILDERNESS VERSUS CIVILIZATION ASREFLECTED IN COOPER\'S THE LAST OF THE MOHICANS AND THE PRAIRIE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
This thesis is a study about the coming of civilization brought by the immigrants to the American wilderness at the early seventeenth century up to the early nineteenth century in James Fenimore Cooper\'s The Last of The Mohicans and The Prairie, and about how far it is reflected by Cooper in the two works.This study is conducted by doing library research which is focused on bibliographical sources related to the topic discussed. This is done by collecting data from both of the published materials and the unpublished materials. This is a work of American studies which emphazises its principle of the interdisciplinary concept. Since literary works become the object of this research, literary theories, in this case the objective and expressive approaches are first applied. hi order to understand Cooper\'s vision about the American phenomenon as depicted in the two novels, approaches from other disciplines are also applied, namely, a) history, to understand the relevant important events in the past, b) culture, to understand the culture of the immigrants and the Indians, and c) ecology, to understand the ecosystem of American wilderness.Cooper\'s experiences living near the quiet, peaceful, and beautiful forest and lake Otsego and the immigrants, motivated him to write the two literary works. In that area, Cooper saw some changes such as the beginning disappearance of wilderness and the persecution of the Indians. Cooper witnessed the changes as the effect of the immigrants\' greedy activities. To Cooper, this was a sign of danger if earning a living from nature does not go simultaneously with the attitude of appreciation of nature. The attitude of appreciation of wilderness can avoid people from greed. In the works, Cooper shows the immigrants\' greed through the conflicts he creates suchas the conflict between France and England and between the immigrants and the Indians. The conflicts happened because of the immigrants\' superiority in the New world. Cooper also shows that the conflicts can bring about human tragedy. Beyond those conflicts, actually, nature has served their life. In the fertile, rich, beautiful, and peaceful place they can live peacefully and harmoniously without cutting trees, killing the animals, and usurping the Indians. The data in the works have been supplemented by the historical, cultural, and ecological data which describe the phenomenon mentioned by Cooper.\r\nFrom the analysis, it is found that Cooper has a noble view for the survival of human beings and their natural environment. Cooper thinks that the greedy attitude or the immoralities of the immigrants towards the rich, fertile, beautiful, and free land, can lead them to destruction. Cooper believes that naturally people have to earn their living, but to Cooper the most important thing is moderation. Cooper\'s concept of moderation here can bring people to a stability: stability between man and man, man and nature, and man and his God.